How to write a manifesto - Hanna, Julian (2013)
That is to say, an avant-garde manifesto: a sort of rough the Looking-Glass reflection of the more common strangeness of the political manifesto. All manifestos are distorted and extreme; they are wish-lists of the overly ambitious, of little Napoleons. But the avant-garde manifesto is especially bonkers, blending revolutionary zeal, dramatic performance, and an insatiable thirst for novelty to create a singularly attractive, circus-like delirium. Who is not electrified upon first reading The Founding and Manifesto of Futurism (1909), the rant that launched a thousand imitators? F.T. Marinetti, futurist-in-chief, summed up his manifesto formula in two key words: “violence and precision.” The avant-garde manifesto would channel the anarchic energy of the new century into a literary form that was seductively strong and thrillingly direct.